The Influence of Product Quality and Service Quality on Online Through Digital Marketing as Intervening Variables During the COVID-19 Pandemic - Saiful Ukamah; Sigit Hermawan; Supardi Supardi; Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to identify and answer some of the problems that exist in the Marketplace related to Product Quality, Service Quality and Purchase Decisions through Digital Marketing. Based on the questionnaire that will be answered by the respondent, the researcher can find out the results that will be obtained and describe how the respondent spends. This research method uses quantitative, in order to facilitate research in generating the existing variables in accordance with using questionnaires distributed by researchers to respondents at PGRI Ronggolawe University, Sunan Bonang University, STIE Muhammadiyah Tuban and IIK Nahdlatul Ulama Tuban. The sampling technique in this study is probability sampling. The method used is simple random sampling. The results of this study indicate that, Product Quality has positive results and effects and has a direct significant result on the Purchase Decision variable. Service Quality has positive and significant results and influence on the Purchasing Decision variable. Product quality has positive and not significant direct results and influence on the purchasing decision variable through digital marketing as the intervening variable. and Service Quality has positive and not significant results and direct influence on the variable of Purchase Decision through Digital Marketing as the intervening variable.